2014
DOI: 10.1111/acer.12419
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Examination of Different Etiological Pathways to Alcohol Use and Misuse

Abstract: Background: Sher, Grekin, and Williams (2005) pointed out the existence of 4 main etiological, but not mutually exclusive, models that might explain the development of alcohol use and misuse. The aim of the present study was to explore 3 of these 4 pathways in which psychological (personality and drinking motives) and environmental (child maltreatment) variables may play a relevant role: positive affect regulation, negative affect regulation, and deviance proneness.Methods: Three hundred and fourteen young adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
56
2
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 46 publications
(74 reference statements)
10
56
2
7
Order By: Relevance
“…Moreover, the metaanalysis of Steel, Schmidt, and Shultz (2008) indicated that extraversion and neuroticism broad domains were the best predictors of subjective wellbeing. In relation to the second outcome, as expected, extraversion and conscientiousness presented positive and negative correlations respectively to alcohol use (Mezquita, Ibáñez, Moya, Villa, & Ortet, 2014). However, we did not find the hypothesized negative correlation between agreeableness and alcohol consumption.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, the metaanalysis of Steel, Schmidt, and Shultz (2008) indicated that extraversion and neuroticism broad domains were the best predictors of subjective wellbeing. In relation to the second outcome, as expected, extraversion and conscientiousness presented positive and negative correlations respectively to alcohol use (Mezquita, Ibáñez, Moya, Villa, & Ortet, 2014). However, we did not find the hypothesized negative correlation between agreeableness and alcohol consumption.…”
Section: Discussionsupporting
confidence: 53%
“…También cabe mencionar que los resultados anteriores sobre EA y diferentes patrones de uso de alcohol durante la semana y en fin de semana se obtuvieron, en parte, con esta misma muestra (Camacho et al, 2013;Ibáñez et al, 2015;Mezquita et al, 2015). De todas maneras, otros estudios sobre variables relacionadas, tales como los motivos por los cuales uno bebe, también han mostrado asociaciones más altas entre los motivos para beber y las UBEs en fin de semana que con las UBEs entre semana en muestras de adolescentes (Mezquita et al, 2018) y de adultos (Mezquita, Ibáñez, Moya, Villa, y Ortet, 2014;Studer et al, 2014). Conjuntamente, dichos hallazgos sugieren que cuando se consumen grandes cantidades de alcohol en fin de semana, las EA sobre los efectos positivos del uso de alcohol y las motivaciones hacia experimentar dichos efectos pueden jugar un papel destacable en la decisión de beber.…”
Section: Discussionunclassified
“…Varios estudios han sugerido que cada una de las cinco categorías de motivos de consumo de alcohol se relaciona con patrones específicos de consumo de alcohol entre adultos jóvenes. Los motivos de animación tienen una relación fuerte con el consumo de alcohol durante el fin de semana (Kuntsche y Cooper, 2010;Mezquita, Ibáñez, Moya, Villa y Ortet, 2014) e indirecta con problemas resultantes del consumo de alcohol (Mezquita, Ibáñez, Moya, Villa y Ortet, 2014;Mezquita, Ruipérez y Stewart, 2010). Los motivos sociales están relacionados con la frecuencia y la cantidad, pero no con los problemas derivados del consumo de alcohol (Grant, Stewart, O'Connor, Blackwell, y Conrod, 2007;Kuntsche, Knibbe, Gmel y Engels, 2005).…”
unclassified